VD_FINDINFO Arrêt / 2025 / 685 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
AA, REJET DE LA DEMANDE, REVENU D'INVALIDE, REVENU SANS INVALIDITÉ | 15 LAA, 18 al. 1 LAA, 19 al. 1 LAA, 24 al. 1 LAA, 36 OLAA